Incidence Of Leaf Spot (Cercospora Spp.) On Plantspeanuts Arachis Hypogaea L.) In Kawangkoan District West - Aldio Fresyelin Lolowang; Berty H. Assa; Henny V. G. Makal; Diane D. Pioh (Jurnal Agroekoteknologi Terapan, 2022)
The purpose of this research is to identify the composition of traditional market waste, to The incidence of leaf spot disease in peanut plants is strongly influenced by temperature and humidity, for the development of the disease can occur throughout the year. If there is a source of inoculum, peanuts planted in any month will have the opportunity to be infected with leaf spot disease. The purpose of this study was to determine how big the incidence of this leaf spot disease was in peanut plants in the West Kawangkoan sub-district. This research took place from March to May 2021, using a survey method by purposive sampling. Observations in the three villages were carried out diagonally with a plot size of 2 X 2 M for 3 weeks. Morphological observations were carried out in the Pest and Plant Diseases laboratory. The results of this study indicate an increase in attacks. The incidence of leaf spot disease in the three villages was 99.19% for Kayuuwi Village, Kayuuwi Satu Village was 99.08%, and Kanonang Village was 98.56%. The average incidence of disease in West Kawangkoan District is 98.94%. Key-words: Incidence, Cercospora spp., Leaf Spot Disease Abstrak Insidensi penyakit bercak daun pada tanaman kacang tanah sangat di pengaruhi oleh suhu dan kelembaban, untuk perkembangan penyakit tersebut dapat terjadi sepanjang tahun. Jika terdapat sumber inoculum, kacang tanah yang ditanam pada bulan apapun akan berpeluang untuk terinfeksi penyakit bercak daun. Tujuan dari penelitian ini untuk mengetahui seberapa besar insidensi dari penyakit bercak daun ini pada tanaman kacang tanah di kecamatan Kawangkoan Barat. Penelitian ini berlangsung dari bulan Maret-Mei 2021, menggunakan metode survey secara purposive sampling. Pengamatan di ketiga desa dilakukan secara diagonal dengan ukuran petak 2 X 2 M selama 3 minggu. Untuk pengamatan morfologi dilakukan di laboratorium Hama dan Penyakit Tumbuhan. Hasil penelitian ini menunujukkan adanya peningkatan serangan. Insidensi dari penyakit bercak daun di ketiga desa sebesar 99,19% untuk Desa Kayuuwi, Desa Kayuuwi Satu sebesar 99,08%, dan Desa Kanonang sebesar 98,56%. Rata – rata insidensi penyakit di Kecamatan Kawangkoan Barat 98,94%. Kata Kunci : Insidensi, Cercospora spp., Penyakit Bercak Daun